1999
DOI: 10.1139/t99-028
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-thaw dewatering of oil sands fine tails

Abstract: Laboratory and field experiments demonstrate that substantial dewatering occurs when the waste clay from oil sands operations is subjected to one cycle of freeze-thaw. The enhanced permeability resulting from the freezing process causes further dewatering and accompanying strength increases during post-thaw consolidation. The findings presented here were guided by a number of different materials handling scenarios which take advantage of the freeze-thaw process and are driven by the appropriate geotechnical, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Thomachot and Matsuoka, 2007). Such consolation can result from freeze-thaw cycling of saturated fine-grained soils (Chamberlain and Gow, 1979) and mine tailings (Dawson et al, 1999), where it causes a net decrease in the void ratio and an increase in permeability. The freeze-thaw behaviour of the chalk was qualitatively similar to that of frostsusceptible soil because not only did ice segregation occur (Section 4.3.)…”
Section: Freeze-thaw Consolidationmentioning
confidence: 99%
“…Thomachot and Matsuoka, 2007). Such consolation can result from freeze-thaw cycling of saturated fine-grained soils (Chamberlain and Gow, 1979) and mine tailings (Dawson et al, 1999), where it causes a net decrease in the void ratio and an increase in permeability. The freeze-thaw behaviour of the chalk was qualitatively similar to that of frostsusceptible soil because not only did ice segregation occur (Section 4.3.)…”
Section: Freeze-thaw Consolidationmentioning
confidence: 99%
“…Besides presenting new challenges to our understanding of colloidal physics, the self-organization of freezing colloids plays an important role in many natural and technological processes. The phenomenon underlies frost heave and patterned ground [7,8], influences the success of cryopreservation [9], and provides a mechanism for the remediation of contaminated clay [10,11]. At low initial particle concentrations it is possible to remove the segregated ice by freeze drying to yield microaligned porous materials with uses in bioengineering and microfluidics [4,12].…”
mentioning
confidence: 99%
“…The depth of ice that can be melted in a given year (based on works by Martel (1989) and Dawson et al (1999)) needs to be confirmed in the field, on site. The melting depth will determine the size of the freezing area required.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the retaining structure was based on an annual treatment of 20 million m 3 /year of typical oil sands process water (half of the freshwater intake volume) and the thickness of ice that can be frozen or thawed annually. Based on previous freeze -thaw research on oil sands fine tails, the maximum thickness of ice produced each year in the Fort McMurray region is governed by the thawing season (Martel 1989, Dawson et al 1999. The estimated thickness of ice that can be melted in one year is 4.5 m. The current design utilized 16 individual containment (freezing) cells, each 545 m6545 m in plan, capable of storing ice 4.5 m thick (figure 3).…”
Section: System Designmentioning
confidence: 99%